Mechanical Impedance Matching Using a Magnetic Linear Gear - Ignacio Valiente-Blanco; Cristian Cristache; Juan Sanchez-Garcia-Casarrubios; Fernando Rodriguez-Celis; Jose-Luis Perez-Diaz (Shock and Vibration)
As part of the Fp7 Clean Sky Project, a linear magnetic gear prototype, called Z-transmitter, for aerospace application was designed, built, and tested. It demonstrates a maximum force capacity of 4700 N at 25°C and 4500 N at 90°C. Force ratio between slow and fast stages remains constant and equal to the design value: 7.0. The behavior of the real Z-transmitter as a mechanical impedance matching device when any stiffness is attached to the fast stage including the limit cases of a blocked fast stage or a free to move fast stage is experimentally explored. Although the real Z-transmitter deviates from the ideal, frictionless and massless, device, it still provides an impedance matching effect large enough to potentially become an extremely useful technology for vibration control when combined with other elements such as dampers, springs, or active elements.